50.6k views
5 votes
If p(x) = 2x2 – 4x and q(x) = x – 3, what is (p*q)(x)?

2x2 – 4x + 12
2x2 – 16x + 18
2x2 – 16x + 30
2x2 – 16x + 15

User Josketres
by
5.7k points

2 Answers

4 votes
C. 2x^2- 16x +30 <--- answer
User VnoitKumar
by
6.3k points
3 votes

Answer:

(p*q)(x) = 2x² - 16x + 30 .

Explanation:

Given : If p(x) = 2x² – 4x and q(x) = x – 3.

To find : what is (p*q)(x)

Solution : We have given p(x) = 2x² – 4x and q(x) = x – 3.

(p*q)(x)

p(x) = 2x² – 4x

(p*q)(x) = 2( x -3)² – 4(x -3).

(p*q)(x) = 2 ( x² + 9 - 6x ) - 4x + 12 .

(p*q)(x) = 2x² + 18 - 12x - 4x + 12 .

(p*q)(x) = 2x² - 16x + 30 .

Therefore, (p*q)(x) = 2x² - 16x + 30 .

User CaptRespect
by
6.0k points